ANALISIS MOTIVASI KONSUMEN DALAM PEMBELIAN PRODUK ELEKTRONIKA - MISBAHUL ANWAR (FE UMY, 2015)
Eleclronics inrluslry, cspcciully tclcvi,tiott,,seent-s to be increasiuglv pr,,nti,ting i)t arcordonce wilh the inLreusing prorpcrity In the .sonrc linte, hov,etter. it is morc conlpelilive because of the entrancc of ntore utd nore teleyision pr.otlucers fu morket place The producers necd,lherefire. to hdt)ecerlairr attitlrde in reaching beller under,standing on lhe conr;uners tendencies in chrnsing products in purcha,sing laleyision. TIta current sttrclv hcts tltree purposcs. Thel o'e ( 1) to identil, hoy, fir the incorue. educalion, antl.job vqriables gNe thcir itfluencc on fl1c c()tl,tu rcrs lotiy.ttion in choosittg products in purclrusing color telcyisiorl, (2) to i(lentify the yuriublcs nost drnninuntly influence cotl:jumers moliyetion in choo,sing products trt purchashg c:olor teleyision, (3) lo identi.fy whether therc arc dilferences in cort,suncr.\ ntotiration in choo.sing producls in purchasing color televi,;io,n. it light of the. difference of intone retâ‚¬ To neasure thc :;h'ength o/ consutTtcr.\ nlotiyation hy usng lhc ('lark H l uodel. Based on the re,sult of tha tmalysr,s it r knou,n lhat lhere utc two consunlers motiyotion tendencies in r,rcs o;f thc dillercncc it the inconte leyel lin the con.sumers with low letel income, the moti\).ttion irr getinirg the econrnnic merit, the euse ond technology reprcsents .factc.trs receiyed fiijor uttentidn of cbnsumers, whilc /br the cinsumers with nidle and high inconre level, tllc totivatiotl in gctining the etononticvt(rrt, thc ett,se uncl tuclr nolog! reprcvnls fitctors receitccl m(ioi o ention of cons14 rcr.s And, ccr.tnonic tlxotiration rcprcsenls tha ospccl rcceiyed !je(ondary alrcntion ufier noking uses of the cuse and lechnolopgt Gcnarallv, narit of expression yoluc hcc:omcs lhe .tspect recciyed lhe sntellest ultcntiott hoth in tlle consluner.\ \1,ith Iov, ntidle, and high level tnconrc